2001
DOI: 10.3109/08977190109001089
|View full text |Cite
|
Sign up to set email alerts
|

The Sequential Activation and Repression of the Human PDGF-B Gene During Chronic Hypoxia Reveals Antagonistic Roles for the Depletion of Oxygen and Glucose

Abstract: Hypoxia and glucose deprivation, are important during many physiological and pathological processes. Cells respond to these stimuli by activating genes involved in the regulation of metabolism and angiogenesis. Platelet derived growth factor-B (PDGF-B) is involved in the regulation of angiogenesis and tumour progression and is induced by hypoxia. Most known hypoxia-induced genes are activated by the hypoxia inducible factor (HIF-1), via its binding to specific response elements. The mechanism of hypoxic induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Although previous studies have shown that PDGF-B mRNA expression is regulated by hypoxia and HIF-1 in other cell types (24)(25)(26), it was not established whether PDGFB is a direct HIF-1 target gene, which requires the identification of a HIF-1-binding site within the context of a functional hypoxia response element. To address this question, we identified seven matches to the consensus HIF-binding site (HBS) sequence 5′-[A/G]CGTG-3′ in the human PDGFB gene (HBS1-7; green triangles in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies have shown that PDGF-B mRNA expression is regulated by hypoxia and HIF-1 in other cell types (24)(25)(26), it was not established whether PDGFB is a direct HIF-1 target gene, which requires the identification of a HIF-1-binding site within the context of a functional hypoxia response element. To address this question, we identified seven matches to the consensus HIF-binding site (HBS) sequence 5′-[A/G]CGTG-3′ in the human PDGFB gene (HBS1-7; green triangles in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of candidate hypoxia response elements in the PDGFB genomic sequence, including a candidate in the 5′-flanking sequence that previously was found to be nonfunctional (25), revealed that HIF-1, but not HIF-2, binds selectively to a site in intron 3 to activate PDGFB transcription, thereby delineating the molecular mechanism underlying previous observations of HIF-1-dependent induction of PDGF-B in hypoxic cells (24,32,33). Because coexpression of HIF-1α and PDGF-B in BCCs was required to establish the relevance of our findings, we confirmed that PDGF-B + cells in breast cancer orthografts were also HIF-1α + .…”
Section: Discussionmentioning
confidence: 99%
“…67 An HRE is also present in the PDGFB gene, although this may not necessarily be responsive to hypoxia. 85 PDGFB protein is secreted by podocytes during early glomerular development, which may be an important signal for recruitment of mesangioblasts, which express the PDGFB receptor, PDGFRβ. 86 Both PDGF and PDGFRβ become confined to the mesangium in later developmental stages, which may provide autocrine signals required for maturation of the mesangium.…”
Section: Assembly Of the Gbm Laminin And Type IV Collagen Networkmentioning
confidence: 99%
“…86 Both PDGF and PDGFRβ become confined to the mesangium in later developmental stages, which may provide autocrine signals required for maturation of the mesangium. 85 Axonal guidance receptors and ligands are also found in developing glomeruli, as they are in developing vessels elsewhere in the embryo. [87][88][89] For example, neuropilin-1 (Np1), a co-receptor with VEGFR2 for VEGF 164 (but lacking a cytoplasmic signaling motif ), immunolocalizes to glomerular endothelial cells.…”
Section: Assembly Of the Gbm Laminin And Type IV Collagen Networkmentioning
confidence: 99%
“…Similarly, the PDGFB gene promoter contains an HRE, although by itself it may not be functionally responsive to hypoxia (67). Mesangial cells are derived from metanephric precursors that do not express Flk1 and therefore are distinct from the endothelial developmental pathway (68).…”
Section: Role For Hif In Metanephric Kidney Developmentmentioning
confidence: 99%